PENGEMBANGAN SOAL TES COMPUTATIONAL THINKING PADA MATERI PECAHAN DI SEKOLAH DASAR MENGGUNAKAN RASCH MODEL - Andra Andaru (COLLASE (Creative of Learning Students Elementary Education), 2022)
This study aims to develop a computational thinking-based problem-solving test instrument  accompanied by analysis using Rasch modeling. This research uses a design research  design with the Reeves model design-based research (DBR) method. The participants of this study were class VI students of SDN 10 Regol, Garut Regency. The results of this study are in the form of computational thinking-based problem-solving test instrument products  totaling 13 multiple-choice questions with four levels of difficulty, namely very easy, easy, medium, and difficult. The test instrument product has been declared feasible after validation by experts, trials and revisions twice, and the results of analysis through Rasch modeling.